2021
DOI: 10.3390/en14175438
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Plants and Business Models: A New Rural Development Perspective

Abstract: The paper evaluates the rural development (RD) contribution of local economic activities (LEAs), whether generated or affected by the proximity of renewable energy plants (REPs). The study also informs about LEAs’ role as co-players in the fight against climate change. Semi-structured research interviews have been applied to identify LEAs’ BM (business model) in Andalusia, Murcia, and Catalonia, autonomous communities of Spain. Most LEAs present a BM based on the RE plant, and others do not, but they still con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Van Vuuren et al [57] found that a strong transition to resource efficiency, sustainable production practices and human development investment could lead to the use of RE, less land use and lower greenhouse gas emissions caused by agriculture. Similarly, Prados et al [58] assessed the contribution of local economic activities to rural development, whether they are created by or influenced by the vicinity of RE installations. The findings revealed that some local economic activities, due to their interconnection with large RE plants, can generate a significant number of employment opportunities.…”
Section: Literature Review On Innovation Adoptionmentioning
confidence: 99%
“…Van Vuuren et al [57] found that a strong transition to resource efficiency, sustainable production practices and human development investment could lead to the use of RE, less land use and lower greenhouse gas emissions caused by agriculture. Similarly, Prados et al [58] assessed the contribution of local economic activities to rural development, whether they are created by or influenced by the vicinity of RE installations. The findings revealed that some local economic activities, due to their interconnection with large RE plants, can generate a significant number of employment opportunities.…”
Section: Literature Review On Innovation Adoptionmentioning
confidence: 99%
“…However, the academic community has not yet explored the interaction mechanism between the behavior of various stakeholders in the NIMBY conflict and the macro-environment. Although scholars have also attempted to explore the relationship between stakeholders, for example, Prados studied the relationship between economic activities and rural development, treating enterprises and residents as key players in NIMBY conflict in their neighborhoods [39]. However, it is undeniable that in the management context of China, the construction site selection of NIMBY facilities cannot be separated from the government's leadership or support, and current research has overlooked the government as a key subject.…”
Section: Introductionmentioning
confidence: 99%
“…To align with the Sustainable Development Goals (SDGs), it is necessary to integrate renewable energy projects into regional development strategies and establish novel governance models to effectively support the energy transition [13]. At this level, investigating renewable energy investment in the community for sustainable energy systems, autonomy, development, and circular economies is necessary.…”
Section: Introductionmentioning
confidence: 99%